The reality of including the dimensions of digital citizenship in the courses of my eternal language in the intermediate stage in the Kingdom of Saudi Arabia - Al-Dosari, Mashael Saleh; Al-Zahrani, Azza Hashem (Journal of Curriculum and Teaching Methodology, 2024)
This research aims to explore the incorporation of dimensions of digital citizenship in the curriculum of "Laghati Al Khalida " in middle school education in the Kingdom of Saudi Arabia. The descriptive method was used with a content analysis approach. The research population consisted of all the "Laghati Al Khalida" curricula taught in the first, second, and third grades of middle school, totaling nine textbooks taught in the first, second, and third semesters of the academic year (1444 H). To achieve the objective, the researchers prepared a list of dimensions of digital citizenship that should be included in the "Laghati Al Khalida" curriculum in the middle school. The final list consisted of seven dimensions: digital access, digital behavior rules, digital law, digital communication, digital culture, digital commerce, and digital security. includes 32 indicators. Based on this, a content analysis tool was developed. The results showed that the term "digital citizenship" was not included in the " Laghati Al Khalida" curriculum for middle school. However, the curricula included all dimensions of digital citizenship to varying degrees, with a very low average inclusion rate of 14.3%. Digital culture had the highest inclusion rate at 43.7%, followed by digital access at 40.4%, digital communication at 9.6%, digital law at 2%, digital behavior rules and digital security at 1.8%, and finally digital commerce at 0.7%. The researchers made several recommendations, including considering the greater inclusion of dimensions of digital citizenship when developing the "Laghati Al Khalida" curriculum for middle school education in Saudi Arabia, according to a well-thought-out plan. They also recommended incorporating linguistic units based on the technological approach in the "Laghati Al Khalida" curriculum, including activities, topics, and texts that promote students’ awareness of digital citizenship.